2020
DOI: 10.3390/sports8040052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One Versus Two Doses of a Multi-Ingredient Pre-Workout Supplement on Metabolic Factors and Perceived Exertion during Moderate-Intensity Running in Females

Abstract: The primary purpose of this study was to examine the acute effects of one versus two doses of a multi-ingredient pre-workout supplement on energy expenditure during moderate-intensity treadmill running. In addition, our second aim was to investigate the responses of associated metabolic factors (i.e., substrate utilization, measures of gas exchange), perceived exertion, and resting cardiovascular variables with one and two doses of the pre-workout supplement. Twelve females (mean ± SD: age = 25.3 ± 9.4 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
1
5
2
Order By: Relevance
“…For example, 3 mg·kg -1 of caffeine has been shown [ 7 , 30 ] to have no effect compared to the 6 mg·kg -1 of caffeine used in the present study and other investigations [ 7 ] that demonstrated increases in energy expenditure. Collectively, these findings [ 7 , 23 , 24 , 27 , 28 , 29 ] suggested that other ingredients in the present preworkout supplement with moderate levels of caffeine (<260 mg or <3.1 mg·kg −1 ) may have provided a synergistic effect that increased energy expenditure.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…For example, 3 mg·kg -1 of caffeine has been shown [ 7 , 30 ] to have no effect compared to the 6 mg·kg -1 of caffeine used in the present study and other investigations [ 7 ] that demonstrated increases in energy expenditure. Collectively, these findings [ 7 , 23 , 24 , 27 , 28 , 29 ] suggested that other ingredients in the present preworkout supplement with moderate levels of caffeine (<260 mg or <3.1 mg·kg −1 ) may have provided a synergistic effect that increased energy expenditure.…”
Section: Discussionmentioning
confidence: 89%
“…These results were surprising given that the caffeine content (<260 mg or <3.1 mg·kg −1 ) of the preworkout supplement was approximately half of the caffeine condition (496 ± 52 mg or 6.0 mg·kg −1 ). Previous studies [ 23 , 27 , 28 , 29 ] have shown that preworkout supplements provide positive effects on resting energy expenditure across a wide range of caffeine content (150–340 mg), whereas preworkout supplements with these same doses (i.e., 150 and 300 mg caffeine) had no effect during moderate-intensity exercise [ 24 ]. The influence of caffeine supplements alone on energy expenditure, however, appears to be dependent on the size of the relative dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations